Core Spun Yarns for Warm Clothing - JAGAJANANTHA, P.; MANDHYAN, P. K.; KRISHNA PRASAD, G.; PATIL, SHARMILA; SENTHILKUMAR, T.; ARPUTHRAJ, A.; PATIL, P. G. (Cotton Research Journal, 2021)
Smart textilesÂ are materials and structures that sense and react to environmental conditions or stimuli, such as those from mechanical, thermal, chemical, electrical, magnetic or other sources. The research work focus on the heat generating fabrics using low voltage power supply such as battery. For this purpose, conductive yarns were produced in core-sheath spinning machine and their heat generating properties were reported at different DC power supply. The core part was the metal wires (NiCr, NiCu, FeNi and Steel,) and the sheath part was cotton fibres. The maximum heat achieved from 12V power supply within 5 minutes is observed as 120 Â°C from NiCu wrapped with cotton fibres.